THE INFLUENCE OF PERSONAL LIFE DEVELOPMENT AS AN INDIVIDUAL DURING ADOLESCENCE: Pengaruh Perkembangan Kehidupan Pribadi sebagai Individu pada Masa Remaja 1 - Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2024)
Individual personal life is a life that is whole and complete and has special or unique characteristics. A person's personal life involves various aspects, including emotional, social-psychological, socio-cultural, and intellectual abilities which are integrated in an integrative manner with the environmental factors of his life. At the beginning of life, in order to lead to a more mature pattern of personal life, individuals will strive to live independently, in the sense of being able to take care of themselves by managing and meeting their needs and carrying out their daily duties and responsibilities. For this reason, it is necessary to have the ability to master situations in the face of various stimuli that can disrupt personal stability. In addition, in personal life harmony between physical and non-physical needs is needed. Physical needs, for example someone needs to breathe freely, need to eat well, drink enough, enjoyment, happiness, security, and so on. With regard to the socio-psychological aspect, every person needs the ability to master his attitudes and emotions as well as a means of communication to socialize. This is seen as a whole and complete in the form of steady behavior and actions. Thus the problem of personal life is a form of integration between physical, socio-cultural and psychological factors. An individual also needs recognition from other parties about his self-esteem, both from his own family and from society in